Kontribusi Supervisi Akademik Kepala Madrasah dan Disiplin Guru terhadap Kinerja Guru Profesional Madrasah Ibtidaiyah di Kota Banjarmasin - Jumiati Jumiati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the contribution of academic supervision by the headmaster and professional teacher discipline to the professional performance of teachers at Madrasah Ibtidaiyah (MI) in Banjarmasin City. Optimal teacher performance is greatly influenced by both internal and external factors, one of which is academic supervision and work discipline. This research uses a quantitative method with a survey approach and descriptive analysis. Data were collected through questionnaires distributed to 100 teachers from various Madrasah Ibtidaiyah in Banjarmasin City, using random sampling techniques. The results show that academic supervision by the headmaster has a significant positive effect on improving teacher performance, where intensive and directed supervision can increase teachers' motivation and teaching competencies. In addition, professional teacher discipline also proves to have a significant contribution to improving teacher performance, where a high level of discipline correlates with an improvement in the quality of classroom learning. Overall, this study concludes that both academic supervision by the headmaster and professional teacher discipline simultaneously have a positive impact on the professional performance of teachers, which in turn contributes to the improvement of education quality in Madrasah Ibtidaiyah in Banjarmasin City. Therefore, improving the quality of supervision and teacher discipline should be a primary focus for the education management at Madrasah Ibtidaiyah.